CYBERETHNOGRAPHY AND ETHNIC IDENTITY: A CASE STUDY OF THE SHAPSUGS OF THE WESTERN CAUCASUS - Kurinskih, Polina Aleksandrovna (History, Archeology and Ethnography of the Caucasus, 2025)
The complexity of identifying ethnosocial processes in multiethnic areas requires flexible research algorithms and a wide array of sources. This article addresses the challenge of correlating socio-economic and cultural-ethnic processes as they are reflected in both virtual and real-world spaces. The focus is on the methods and algorithms of cyberethnographic research and their potential application in studying ethnosocial processes found in social communication forms within rural enclaves of multiethnic mountain ecosystems. The primary goal of this work is to determine the informational capacity and validity of cybersources and research techniques. This is achieved through an analysis of field ethnographic materials from the Shapsugs – a small, indigenous people of the Western Caucasus. The Shapsugs are a subethnos of the Adyghe whose traditional territories and resource management practices are located adjacent to the Sochi National Park, which has led to a transformation of their livelihood and culture. The research methods employed include content analysis of photo and video materials from cyberspace (social networks, blogs, and official institutional websites), as well as classic fieldwork techniques such as observation, interviews, and expert surveys. The author concludes that the object of cyberethnography is currently focused on individual cases of “ethnicity” and ethnic self-identification on the internet. The primary methods used in this field are surveys, interviews, content analysis, and observation. The case study of the Shapsugs revealed the dynamic nature of changes in social communication systems that affect ethnic interests. By examining the traditional nature management and culture of the Shapsugs in the Sochi Black Sea region, we have outlined an algorithm for identifying latent ethnic processes by synthesizing information from diverse sources. The study demonstrates that when researching ethnosocial processes in remote mountain settlements, it is most effective to combine fieldwork materials with cybersources, as they fit organically into the framework of ethnological examinations. The application of the principle of chronological sections further enhances the ability to identify ethnic processes and trends.
Keywords: ethnic processes; life support system; life support culture; traditional culture; local ethnic groups; small indigenous peoples; Shapsugs; national parks; cyberethnography; digital anthropology